Effects of Additional Mint Leaf (Mentha Piperita, L) Fermentation on the Percentage of Broiler Carcass, Liver and Heart - Nelzi Fati; Debby Syukriani; Nilawati Nilawati (UNIVERSITAS ISLAM LAMONGAN, 2023)
Research with the addition of fermented mint leaves in drinking water aims to determine the effect of treatment on the percentage of carcass weight, liver and heart. This research was carried out for 2 months in the Animal Feed and Nutrition Laboratory and in the broiler cage at the Livestock Production Laboratory, Payakumbuh State Agricultural Polytechnic. This study started from DOC until the age of 35 days, as many as 100 broilers were the subjects, 5 treatments and 4 replications were given. The treatments were without the addition of fermented mint leaves (A), the addition of 0.3% fermented mint leaves in drinking water (B), the addition of 0.6% fermented mint leaves in drinking water (C), the addition of 0.9% fermented mint leaves in drinking water. drinking water (D) and the addition of 1.2% fermented mint leaves in drinking water (E). The basal ration consisted of corn, palm oil meal, soybean meal, fish meal, coconut oil and top mix. The variables measured were the percentage of carcass weight, liver, and heart. The research method used a completely randomized design. The results showed that the addition of fermented mint leaves in drinking water had no significant effect (P>0.05) on the percentage of carcass weight, liver and heart. The conclusion is that the addition of fermented mint leaves in drinking water up to a level of 1.2% can be tolerated by broilers until the age of 5 weeks.